Preparation of a FeZn-based three-dimensional self-supporting electrode and its application in electrocatalytic carbon dioxide reduction
Through the preparation of FeZn-based three-dimensional self-supporting electrode material, the Fe:Zn ratio is regulated to be 3:1, which solves the problems of poor reduction activity of existing iron-based catalysts in CO2RR and strong hydrogen evolution reaction, and achieves high-efficiency and low overpotential carbon dioxide reduction. The Faraday efficiency of CO reaches 86%, which significantly improves the selectivity and stability of the catalyst.
Patent Information
- Application Number
- CN202211159083.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-09-22
AI Technical Summary
The existing iron-based catalysts have disadvantages such as poor reduction activity and strong competitive hydrogen evolution reaction in electrocatalytic carbon dioxide reduction (CO2RR), which is difficult to meet the needs of industrial applications.
The FeZn-based three-dimensional self-supporting electrode material was used to regulate the Fe:Zn ratio to 3:1, and the raw materials such as ferric chloride hexahydrate, zinc nitrate hexahydrate, urea and ammonium fluoride were prepared under mild conditions to form a three-dimensional self-supporting structure with high active sites.
It has achieved efficient catalytic carbon dioxide reduction at low overpotentials, and the Faraday efficiency of CO reaches 86%, which significantly improves the selectivity and stability of the catalyst and broadens the application range of non-precious metal electrocatalysts.
Smart Images

Figure CN115418664B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of a FeZn-based three-dimensional self-supporting electrode material and its electrocatalytic carbon dioxide reduction performance (CO 2 RR). Background Art
[0002] Recycling carbon dioxide through electrocatalysis is one of the ideal ways to alleviate or solve the ecological crisis currently facing mankind. The development of cheap and efficient catalysts is the key to promoting the industrialization of electrocatalytic carbon dioxide reduction. Carbon monoxide is an important industrial raw material. 2 The reduction of CO has important research significance. 2 RR reaction, using a fully sealed dual electrolytic cell, carbon dioxide reduction generally occurs at the cathode: xCO 2 +nH + +ne - →product+yH 2 O, reacts with hydrogen evolution: 2H + +2e - →H 2 (g); The reaction at the anode is the oxygen evolution reaction: 2H 2 O→O 2 +4H + +4e-, H is transferred between the two electrolytic cells through the ion membrane + .CO 2 RR involves multi-electron and multi-proton reaction pathways, and its products are also diverse. Therefore, there are still many fundamental challenges in the electrocatalytic reduction of carbon dioxide: the high overpotential and slow reaction rate of commonly used electrocatalysts; the reaction that selectively generates carbon-based products is difficult to control, and the selectivity of the reduction products is poor; competitive hydrogen evolution reactions in aqueous media are common, etc. At present, how to prepare efficient catalysts with high Faraday efficiency, low overpotential, good selectivity for the target product and high stability has become the key to research and a research hotspot in the field of electrocatalytic reduction of carbon dioxide. According to domestic and foreign studies, highly active precious metal catalysts have good selectivity for CO2 reduction. 2 RR has good reaction performance, but the high-activity precious metals are difficult to apply on a large scale due to their scarce reserves. Therefore, iron-based catalysts, which are abundant on the earth, have become potential alternatives. However, common iron-based catalysts have disadvantages such as poor reduction activity and strong competitive hydrogen evolution reaction, which are difficult to meet actual needs.
[0003] Among the many materials currently being studied, iron has received extensive attention in the field of catalysis due to its abundant reserves on Earth and low price. At the same time, the three-dimensional self-supporting structure has a large open space that can expose more active sites, and mass diffusion is easier. More importantly, the self-supporting structure can avoid the use of polymer binders, which can significantly improve the stability of electrode materials and avoid the tedious subsequent processing and preparation of electrodes. Summary of the invention
[0004] A preparation method of a FeZn-based three-dimensional self-supporting electrode material, the specific steps are as follows:
[0005] (1) First, ferric chloride hexahydrate (FeCl 3 6H 2 O) 1.6218 g (6 mmol), zinc nitrate hexahydrate (Zn(NO 3 ) 2 6H 2 O) 0.5949 g (2 mmol), urea 2.4024 g, ammonium fluoride (NH 4 F) 0.592g are dissolved in 120ml water and stirred for 30min to fully dissolve. The foamed copper is placed obliquely in the reactor, the solution is poured into the reactor 2 / 3 of the way, and the reactor is placed in an oven at 120℃ for 6h.
[0006] (2) After the reaction is completed, take out the mixture, let it cool slightly (do not leave it for too long, and do not take it out at high temperature), take it out, wash it with water and ethanol, and slightly sonicate it to obtain the final product.
[0007] The prepared FeZn-based three-dimensional self-supporting electrode material is washed and ultrasonicated to remove impurities attached to the copper foam during the hydrothermal process. However, the ultrasonication time should not be too long, generally about 30 seconds. (To prevent the loaded catalyst from falling off and affecting the test performance)
[0008] The present invention relates to the preparation and performance of a FeZn-based three-dimensional self-supporting electrode material, which can be applied in the field of electrocatalytic carbon dioxide reduction. When the Fe:Zn ratio is adjusted to 3:1, at a potential of -0.40V vs.RHE, the current density of the catalyst is 10mA·cm -2 , CO Faradaic efficiency is 86%.
[0009] The advantages of the present invention are: simple preparation process, mild conditions, low-cost and readily available raw materials, excellent performance of the prepared electrocatalyst, and broadening the application range of non-precious metal electrocatalysts. The catalyst can be used for electrocatalytic carbon dioxide reduction (CO 2In the field of RR, in the electrocatalytic reduction system with 0.5M KHCO3 aqueous solution as the electrolyte, the selectivity of the catalyst can be changed by adjusting the ratio of Fe and Zn content, and the adsorption capacity of the catalyst for H· and CO· is optimized. When the ratio of Fe and Zn in the electrode material is 3:1, at a potential of 0.4V, its selectivity for CO is as high as 86%. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is the XRD spectrum of the FeZn-based three-dimensional self-supporting electrode material obtained in Example 1.
[0011] Figure 2 XPS spectrum of the FeZn-based three-dimensional self-supporting electrode material obtained in Example 1.
[0012] Figure 3 Scanning electron microscope image of the FeZn-based three-dimensional self-supporting electrode material obtained in Example 1.
[0013] Figure 4 Electrochemical linear sweep voltammetry curves of different Fe and Zn ratios in the FeZn-based three-dimensional self-supporting electrode materials obtained in Examples 1-3 (LSV test in 0.5 mol / L KHCO 3 In the solution, Ag / AgCl electrode was used as reference electrode, graphite electrode as counter electrode, catalytic material as working electrode, and the instrument used was CHI electrochemical workstation. The scanning range during the test was 0-2V and the scanning rate was 5mV / s)
[0014] Figure 5 CO and H at different Fe and Zn ratios in the FeZn-based three-dimensional self-supporting electrode materials obtained in Examples 1-3 2 Faraday efficiency diagram. (A Fuli GC9790II chromatograph equipped with 5A molecular sieve and two porapakQ chromatographic columns was used for gas offline analysis. Among them, the flame ionization detector (FID) was used to analyze the concentration of the reduction product CO, and the thermal conductivity detector (TCD) was used to analyze the concentration of the reduction product CO. The electrochemical test condition parameters are similar to Figure 4 same). DETAILED DESCRIPTION
[0015] The present invention is further described in detail below through specific examples.
[0016] For the pretreatment of the foam copper, it was first rinsed with deionized water, acetone, deionized water, anhydrous ethanol and deionized water in sequence, then added to 36.5% concentrated hydrochloric acid and ultrasonicated for 5 minutes, then taken out and quickly rinsed with water repeatedly until the hydrochloric acid on the surface of the foam copper was washed away, and then ultrasonicated in deionized water and anhydrous ethanol for 30 minutes respectively before use.
[0017] Use copper foam as the substrate, and cut the square sheet substrate with a thickness of 0.5 mm into 2×4 cm 2 .
[0018] Embodiment 1:
[0019] Preparation of FeZn-based three-dimensional self-supporting electrode materials with a Fe:Zn ratio of 3:1: 3 6H 2 O) 1.6218 g (6 mmol), zinc nitrate hexahydrate (Zn(NO 3 ) 2 6H 2 O) 0.5949 g (2 mmol), urea 2.4024 g, ammonium fluoride (NH 4 F) 0.592g was dissolved in 120ml water, stirred at 450r / min for 60min, mixed evenly, and the solution was obtained. The treated copper foam was placed obliquely (the surface of the copper foam was at a 45-degree angle to the bottom of the reactor parallel to the horizontal plane) in the reactor, and the solution was poured into the reactor at a height of 2 / 3 (the liquid volume was 2 / 3 of the volume in the reactor), and the copper foam was located below the liquid surface, and placed in an oven at 120℃ for 6h. After the reaction, the solution in the reactor was allowed to cool slightly (not for too long, and not to be taken out at high temperature) to 40℃, the copper foam was taken out, washed with deionized water and ultrasonicated for 30s, and finally dried to obtain a FeZn-based three-dimensional self-supporting electrode material with a molar ratio of Fe and Zn of 3:1 on the copper foam to support the catalyst.
[0020] The processes and conditions of the following Examples 2-3 are the same as those of Example 1, and the differences therefrom are described in the following Examples;
[0021] Embodiment 2:
[0022] Preparation of FeZn-based three-dimensional self-supporting electrode materials with a Fe:Zn ratio of 1:1: 3 6H 2 O) 0.5406 g (2 mmol), zinc nitrate hexahydrate (Zn(NO 3 ) 2 6H 2 O) 0.5949 g (2 mmol), urea 2.4024 g, ammonium fluoride (NH 4F) 0.5920g was dissolved in 120ml water, stirred at 450r / min for 60min, mixed evenly, and the solution was obtained. The treated copper foam was placed obliquely (at a 45-degree angle with the bottom of the reactor parallel to the horizontal plane) in the reactor, and the solution was poured into the reactor at a height of 2 / 3 (the liquid volume was 2 / 3 of the volume in the reactor), and the copper foam was located below the liquid surface, and placed in an oven at 120℃ for 6h. After the reaction was completed, it was allowed to cool slightly (not to be left for too long, and not to be taken out at high temperature) to 40℃, and the copper foam was taken out, washed with deionized water and ultrasonicated for 30s, and finally dried to obtain a FeZn-based three-dimensional self-supporting electrode material with a molar ratio of Zn and Fe of 1:1 on the copper foam.
[0023] Embodiment 3:
[0024] Preparation of FeZn-based three-dimensional self-supporting electrode materials with a Fe:Zn ratio of 1:3: 3 6H 2 O) 0.5406 g (2 mmol), zinc nitrate hexahydrate (Zn(NO 3 ) 2 6H 2 O) 1.7849 g (6 mmol), and urea 2.4024 g, ammonium fluoride (NH 4 F) 0.592g was dissolved in 120ml water, stirred at 450r / min for 60min, mixed evenly, and the solution was obtained. The treated copper foam was placed obliquely (at a 45-degree angle with the bottom of the reactor parallel to the horizontal plane) in the reactor, and the solution was poured into the reactor at a height of 2 / 3 (the liquid volume was 2 / 3 of the volume in the reactor), and the copper foam was located below the liquid surface, and placed in an oven at 120℃ for 6h. After the reaction was completed, it was allowed to cool slightly (not to be left for too long, and not to be taken out at high temperature) to 40℃, and the copper foam was taken out, washed with deionized water and ultrasonicated for 30s, and finally dried to obtain a FeZn-based three-dimensional self-supporting electrode material with a molar ratio of Fe and Zn of 1:3 on the copper foam.
[0025] Some structural and performance tests were carried out on the catalyst prepared above.
[0026] Figure 1 The X-ray diffraction (XRD) pattern of the FeZn-based three-dimensional self-supporting electrode material with a Fe:Zn ratio of 3:1 generated in Example 1. Figure 1 It can be seen from Figure 1 It can be seen that the FeZn-based three-dimensional self-supporting electrode material has the same crystal phase structure as FeO(OH). Figure 2 , 3The XPS and SEM characterizations of the FeZn-based three-dimensional self-supporting electrode material in Example 1 prove that we have successfully synthesized a FeZn-based three-dimensional self-supporting electrode material with a molar ratio of Fe and Zn of 3:1, and it belongs to a lamellar bimetallic layered hydroxide structure.
[0027] Figure 2 XPS spectrum of the FeZn-based three-dimensional self-supporting electrode material obtained in Example 1. Figure 2 It can be seen from the XPS full spectrum and fine spectrum that the FeZn-based three-dimensional self-supporting electrode material is composed of Fe, Zn and O elements.
[0028] Figure 3 This is a scanning electron microscope image of the FeZn-based three-dimensional self-supporting electrode material obtained in Example 1. Figure 1 It can be seen that the obtained FeZn-based three-dimensional self-supporting electrode material is a three-dimensional sheet array structure, and its sheets grow perpendicular to the substrate surface, with a thickness (height) range of 30-50nm and an area size range of 1.5-2.0um 2 .
[0029] Figure 4 The catalyst obtained in Example 1-3 is used for electrochemical carbon dioxide reduction (CO 2 RR) Performance test diagram, the test conditions are: 30ml of 0.5mol / L KHCO was transferred into the electrolytic cell. 3 The solution was then fed into different electrolytic cells with CO 2 and Ar gas for 30 min to make the KHCO in different electrolytic cells 3 The solution reaches CO 2 The mixture was saturated with Ar gas, with an Ag / AgCl electrode as the reference electrode, a graphite electrode as the counter electrode, and FeZn-based three-dimensional self-supporting electrodes with different Zn and Fe ratios prepared in Examples 1-5 as the substrate as the working electrodes (the effective working area of the electrode in the liquid was 1.0×1.0 cm 2 , the distance between the counter electrode and the working electrode is 2 cm) and the instrument used is CHI760e electrochemical workstation. (LSV test in 0.5 mol / L KHCO 3 In the solution, Ag / AgCl electrode was used as reference electrode, graphite electrode as counter electrode, FeZn-based three-dimensional self-supporting electrode as working electrode, the scanning range was 0-2V, and the scanning rate was 5mV / s. 2 The test results under an Ar atmosphere reflect the catalyst's ability to electrocatalyze carbon dioxide reduction, and the cathode reduction product is CO. The test results under an Ar atmosphere reflect the catalyst's ability to generate hydrogen, and the cathode product is H 2 . It can be seen from the figure that in CO 2The LSV overpotentials under the atmosphere are all smaller than those under the Ar atmosphere, indicating that the CO2 reduction performance of the three electrocatalysts with different ratios is stronger than the hydrogen evolution performance under the Ar atmosphere.
[0030] Figure 5 CO and H at different Fe and Zn ratios and different potentials in the FeZn-based three-dimensional self-supporting electrode materials obtained in Examples 1-3 2 Faraday efficiency diagram, the test condition is to add 30ml of 0.5mol / L KHCO in the electrolytic cell 3 solution, and then CO is introduced into the electrolytic cell 2 The gas is used for 30 minutes to make the KHCO in the electrolytic cell 3 The solution reaches CO 2 Gas saturation, with Ag / AgCl electrode as reference electrode, graphite electrode as counter electrode, and FeZn-based three-dimensional self-supporting electrode with different Zn and Fe ratios on the basis of copper foam as the three-electrode system of working electrode, the instruments used are CHI760e electrochemical workstation and Fuli GC9790II chromatograph. It can be seen from the LSV curve that the peak potential begins to appear at around -0.20V vs.RHE, so the chronoamperometric test at four potentials of -0.2 to -0.5V vs.RHE was selected, and then a certain amount of the post-reaction gas was introduced into the gas chromatograph using an injection needle to test the composition of the post-reaction gas, and the Faraday efficiency was calculated to judge the product selectivity of the catalyst. It can be seen from the figure that the FeZn-based three-dimensional self-supporting electrode material with a ratio of Fe to Zn of 3:1 has the highest CO Faraday efficiency at -0.4vs.RHE, which can reach 86%, indicating that the carbon dioxide reduction reaction occurring at the cathode of the electrolytic cell under the action of the catalyst is dominant, far greater than the hydrogen evolution reaction, indicating that the catalyst has good product selectivity.
[0031] The present invention relates to the preparation of a FeZn-based three-dimensional self-supporting electrode material and its electrocatalytic carbon dioxide reduction performance (CO 2 RR), the catalyst preparation process is simple, the carbon dioxide reduction overpotential is low, and the selectivity of the catalyst can be changed by adjusting the ratio of Fe and Zn in the electrode material. When the ratio of Fe and Zn in the electrode material is 3:1, at a potential of 0.4V, the Faraday efficiency of CO is as high as 86%, which has good application prospects in the field of electrocatalytic carbon dioxide reduction.
Claims
1. A method for preparing a FeZn-based three-dimensional self-supporting electrode material, characterized in that: Using ferric chloride hexahydrate and zinc nitrate hexahydrate as raw materials, copper foam is used as a substrate in an aqueous solution containing urea and ammonium fluoride, and a FeZn-based three-dimensional self-supporting electrode material supported on copper foam is obtained through hydrothermal synthesis.
2. The preparation method according to claim 1, characterized in that: The specific process is as follows: 0.1-2.0 g of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.2-2.0 g of ferric chloride hexahydrate (FeCl3·6H2O), 2.0-2.8 g of urea and 0.4-1.0 g of ammonium fluoride are dissolved in 50-180 mL of water, and then stirred to obtain a solution; using foam copper as a substrate, the cut foam copper is placed obliquely into a reactor and the stirred solution is added for a hydrothermal reaction at a reaction temperature of 110-140°C and a reaction time of 3 h-24 h. The foam copper is then taken out, washed in deionized water and ultrasonicated, and dried to obtain an electrode sample with a catalyst loaded on the foam copper.
3. The preparation method according to claim 2, characterized in that: The specific process is to dissolve 0.3-1.9 g zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.4-1.8 g ferric chloride hexahydrate (FeCl3·6H2O), 2.1-2.7 g urea and 0.4-0.8 g ammonium fluoride in 60-160 ml water, the reaction temperature is 115-130°C, and the reaction time is 6-12 h.
4. The preparation method according to claim 3, characterized in that: The specific process is to dissolve 0.5-1.8 g zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.5-1.7 g ferric chloride hexahydrate (FeCl3·6H2O), 2.2-2.5 g urea and 0.5-0.6 g ammonium fluoride in 100-120 ml water, the reaction temperature is 120-125°C, and the reaction time is 6-8 h.
5. The preparation method according to claim 2, characterized in that: The copper foam used as the substrate needs to be pretreated before use. The specific process is to rinse it with deionized water, acetone, deionized water, anhydrous ethanol, and deionized water in sequence, then add it to 20-40% concentrated hydrochloric acid for ultrasonic treatment for 5-6 minutes, then take it out and rinse it repeatedly with water until the hydrochloric acid on the surface of the copper foam is washed away, then use deionized water and anhydrous ethanol for ultrasonic treatment for 20-40 minutes respectively before use.
6. The preparation method according to claim 5, characterized in that: The mass concentration of concentrated hydrochloric acid added is 30-38%.
7. The preparation method according to claim 6, characterized in that: The mass concentration of concentrated hydrochloric acid added is 35-37%.
8. The preparation method according to claim 2, characterized in that: After the hydrothermal reaction, the solution in the reaction kettle is placed at 30-80° C., and then the foamed copper is taken out from the solution.
9. The preparation method according to claim 8, characterized in that: After the hydrothermal reaction, the solution in the reaction kettle is placed at 35-70° C., and then the foamed copper is taken out from the solution.
10. The preparation method according to claim 9, characterized in that: After the hydrothermal reaction, the solution in the reaction kettle is placed at 40-50° C., and then the foamed copper is taken out from the solution.
11. The preparation method according to claim 2, characterized in that: The size of the sheet copper foam substrate is cut into 0.5×0.5 cm 2 -4×4 cm 2 Square, 0.1-1.0 mm thick, place the copper foam in the reactor so that the copper foam is completely below the liquid surface; the surface of the copper foam below the liquid surface forms an angle of 40-60 degrees with the horizontal plane.
12. The preparation method according to claim 11, characterized in that: The size of the sheet copper foam substrate is cut into 0.8×0.8 cm 2 -3×3 cm 2 Square, 0.2-0.8 mm thick, place the copper foam in the reactor so that the entire copper foam is below the liquid surface; the surface of the copper foam below the liquid surface forms an angle of 40-55 degrees with the horizontal plane.
13. The preparation method according to claim 12, characterized in that: The size of the sheet copper foam substrate is cut into 1×1 cm 2 -1×2 cm 2 Square, 0.4-0.6 mm thick, place the copper foam in the reactor so that the entire copper foam is below the liquid surface; the surface of the copper foam below the liquid surface forms an angle of 45-50 degrees with the horizontal plane.
14. A FeZn-based three-dimensional self-supporting electrode material with foam copper as a substrate, prepared by the preparation method according to any one of claims 1 to 13.
15. Use of the FeZn-based three-dimensional self-supporting electrode material with copper foam as the substrate as claimed in claim 14 in the process of electrocatalytic carbon dioxide reduction.
16. The use according to claim 15, characterized in that: The specific application conditions are: transfer 20-50mL of 0.2-1.0 mol / L KHCO3 and / or NaHCO3 alkaline solution into the electrolytic cell, then introduce CO2 gas into the KHCO3 or NaHCO3 alkaline solution in the electrolytic cell so that the alkaline solution in the electrolytic cell contains CO2 gas, use a graphite electrode as a counter electrode, and a FeZn-based three-dimensional self-supporting electrode material with foam copper as a substrate as a working electrode, apply current between the counter electrode and the working electrode to reduce carbon dioxide.
17. The use according to claim 16, characterized in that: The specific application conditions are: transfer 25-40 ml of 0.3-0.8 mol / L KHCO3 and / or NaHCO3 alkaline solution into the electrolytic cell.
18. The use according to claim 17, characterized in that: The specific application conditions are: transfer 30-35 ml of 0.5-0.6 mol / L KHCO3 and / or NaHCO3 alkaline solution into the electrolytic cell.
19. The use according to claim 16, characterized in that: CO2 gas is introduced into the KHCO3 and / or NaHCO3 alkaline solution in the electrolytic cell for 20-60 minutes to saturate the solution with CO2 gas.
20. The use according to claim 19, characterized in that: Introduce CO2 gas into the KHCO3 and / or NaHCO3 alkaline solution in the electrolytic cell for 25-50 minutes to saturate the solution with CO2 gas.
21. The use according to claim 20, characterized in that: Pass CO2 gas into the KHCO3 and / or NaHCO3 alkaline solution in the electrolytic cell for 30-40 minutes to saturate the solution with CO2 gas.
Citation Information
Patent Citations
Three-dimensional graphene foamed composite for hydroquinone visual detection
CN109030469A
Ferronickel hydroxide electrocatalyst, preparation method and application thereof, self-powered system and application thereof
CN111313041A